Astrocyte´s RAGE: more than just a question of mood (2018)
Background: Adequate function of the nervous system depends on the balance of glianeuron complex interactions. Astrocytes, in particular, are key elements in this process due to the significant participation of these cells in essential properties of the nervous system such as neuroinflammation, regulation of neurotransmitters, release of gliotransmitters and control of synaptic plasticity, among others. Astrocytes express the receptor for advanced glycation end products (RAGE) which is very important in the recognition of endogenous molecules released in the context of infection, physiological stress or chronic inflammation. RAGE can bind several advanced glycation end products, S100 proteins, HMGB1, amyloid-? and other additional DAMP molecules. The nuclear factorkappa B (NF-?B) transcription pathway is the main intracellular signaling pathway activated by the RAGE receptor, inducing an increase in the expression and release of proinflammatory cytokines. Due to its numerous interactions, RAGE is suspected to be involved in various physiological and pathological processes. Conclusion: It is plausible that a prolonged exposure to RAGE ligands or abnormally increased concentrations of some ligands may induce lengthy periods of intracellular proinflammatory activation, which may induce the appearance of reactive astrocytes involved in the development and/or progression of neurodegenerative disorders. Blocking or reducing the duration of activation of RAGE/NF-?B signaling in astrocytes may become an important therapeutic alternative for the treatment of neurodegenerative disorders in the future.